LEGAL FRAMEWORK OF ENVIRONMENTAL LAW FOR AGRICULTURAL PRODUCTION IN POLAND - Monika Król (Polityki Europejskie, Finanse i Marketing)
In Poland, both in the interwar period, and throughout the communist period, the government policy relating to agriculture marked as the primary goal ensuring the public food security in terms of quantity. The first legislation relating to environmental protection in agricultural activities appeared in the seventies and addressed the problem of prevention of changing agricultural land for non-agricultural purposes, preventing of lowering their fertility and restoring value in use to agricultural land, degraded as a result of non-agricultural activities. After accession to the EU the following served to promote environmentally friendly farming practices: The Code of Good Agricultural Practice (2004) and the rules of the Common Good Agricultural Practice, introduced due to the dependence of financial support in the framework of several measures covered by the RDP for the fulfillment of environmental requirements. These standards related primarily to the requirements of the rational management of fertilizers, plant protection products, management of grasslands, water and soil conservation, rational use of wastewater and sewage sludge, conservation of valuable habitats and species found in agricultural areas, as well as maintaining cleanliness and order on the farm. The harmonization period of the Polish legislation with EU law and the first years of Polish membership in the community provided a very dynamic development of legal regulations relating to environmental protection in agriculture. A call to integrate the objectives of environmental protection, especially biodiversity and agricultural activities can be seen in many acts e.g. which include: emission law, regulation relating to the strenuous and dangerous activities, protection and use of recourses of the biosphere. In conclusions it is important to underline the role of agriculture to the environment. Agriculture is based on the environment, it indisputable delivers environmental public goods but on the other hand agricultural production has its impact to the particular elements of the environment. Including entities involved in agriculture production, into category of entities using the environment regardless of their legal form, is of unquestionable importance in view of the legal instruments of liability for environmental damage, as being guarantees for compliance with the rules in force in this area of the law. The growing use of agri-environment schemes, codes of good agricultural practices, organic farming and financial support for farming in less favored areas have had a positive impact on farmland biodiversity and modern farming in Poland contributes to the conservation of genetic resources, species and habitats.